Information advantages of training employers despite credible training certificates. (5th September 2019) - Mohrenweiser, Jens; Wydra-Somaggio, Gabriele; Zwick, Thomas
Abstract: Employers sponsor general training if they can get an information advantage about the skills of trainees. This advantage might vanish if credible external institutions grade successful training completion. We argue that despite a certificate, training firms can retain an information advantage and can positively select training completers because the training certificate does not capture all relevant skill dimensions. Training firms can get an information advantage on the non-certified skills such as soft skills. We show that the information advantage about non-certified skills can explain why training firms pay higher wages for training completers than outside firms and why employers are able to keep a positive selection of training participants.